Effect of Drying Using Oven on Temperature, Humidity, Moisture Content of Banana Sale Products with Kepok Banana Base Material - Nursyafitri, Ike; Sari, Devi Tangga (Universitas Muhammadiyah Mataram, 2022)
Banana one of the commodities that are widely cultivated by the people of Indonesia. Banana sale is a food processed by ripe bananas which are thinly combed and then preserved by drying. During the drying of the sale of bananas, the water content decreased in terms of temperature and humidity, so a method is needed that canmaintain the water content of banana sale during drying by applying drying technology using an electric oven. The purpose of this study was to determine the effect of oven drying on the temperature, humidity, moisture content of sale bananas with kepok banana as the basic ingredient. This study used a completely randomized design (CRD), the factor used was temperature treatment. Factorial is repeated three times, parameters analyzed were temperature, humidity and moisture content of banana sale drying. The results showed that drying banana sale with a temperature of 60˚C for 12hours gave the best water content compared to temperatures of 40˚C and 50˚C so that it met the SNI quality for a maximum of 15-20% water content of banana sale.